2008
DOI: 10.1002/ijc.23894
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine induces cell proliferation, invasion and epithelial‐mesenchymal transition in a variety of human cancer cell lines

Abstract: Cigarette smoking is strongly correlated with the onset of nonsmall cell lung cancer (NSCLC). Nicotine, an active component of cigarettes, has been found to induce proliferation of lung cancer cell lines. In addition, nicotine can induce angiogenesis and confer resistance to apoptosis. All these events are mediated through the nicotinic acetylcholine receptors (nAChRs) on lung cancer cells. In this study, we demonstrate that nicotine can promote anchorage-independent growth in NSCLCs. In addition, nicotine als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
290
2
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 331 publications
(316 citation statements)
references
References 60 publications
(115 reference statements)
22
290
2
2
Order By: Relevance
“…Exposure of nicotine promotes the invasive and migratory ability of lung cancer cells and transplanted tumor in a mouse model (13,14). In this study, we also found similar effect of nicotine on A549 and H1299 cells; in addition, our results demonstrated that all flavones in Scutellaria inhibited nicotine-induced invasion in both cell lines and migration in A549 cells, and only baicalein suppressed nicotine-induced migration in H1299 cells.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Exposure of nicotine promotes the invasive and migratory ability of lung cancer cells and transplanted tumor in a mouse model (13,14). In this study, we also found similar effect of nicotine on A549 and H1299 cells; in addition, our results demonstrated that all flavones in Scutellaria inhibited nicotine-induced invasion in both cell lines and migration in A549 cells, and only baicalein suppressed nicotine-induced migration in H1299 cells.…”
Section: Discussionsupporting
confidence: 81%
“…carcinoma cells and epithelial-mesenchymal transition (EMT) in lung cancer cells (13,19). Thus, though nicotine itself cannot provoke cancer, it contributes to lung cancer progression already initiated through diverse processes.…”
Section: Flavonoid Components In Scutellaria Baicalensis Inhibit Nicomentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have shown that the decrease in E-cadherin and ␤-catenin with a concurrent increase in fibronectin and vimentin levels is one of the hallmarks of epithelial-mesenchymal transition in lung cancer cells (24). Earlier studies from our lab showed that nicotine induces changes consistent with EMT such as upregulation of mesenchymal proteins like vimentin and fibronectin (9). In the present study, we observed strong positive correlations of ID1 with mesenchymal markers vimentin and fibronectin and also with the ␣7 subunit of nAChR in human tumor samples.…”
Section: Discussionmentioning
confidence: 92%
“…EMT-like changes in an ␣7 receptor-and Src-dependent manner (9). Nicotine can diminish the expression of epithelial markers such as E-cadherin and ␤-catenin and upregulate mesenchymal proteins like fibronectin and vimentin in multiple cell lines, indicative of increased cell motility.…”
Section: Vol 31 2011 Id1 Promotes Lung Cancer Growth 3061mentioning
confidence: 99%